POLA REGISTER DALAM UNGKAPAN NEGATIF PEMBELI PADA FORUM ULASAN E-COMMERCE - Pratama, Aditya; Nurzafira, Istiqomah (Jurnal Membaca Bahasa dan Sastra Indonesia, 2025)
This study examines register patterns in buyers' negative reviews on e-commerce platforms using a sociopragmatic and interactional linguistics approach. It identifies linguistic structures and communication strategies in expressing dissatisfaction, analyzing data through Halliday’s (1978) register components: field, tenor, and mode. Findings indicate that negative reviews predominantly feature informal and expressive language, often breaching politeness norms. Platform characteristics and buyer-seller dynamics further shape linguistic variation. These insights inform businesses and e-commerce platforms on digital communication strategies and effective responses to negative reviews.